The case for development in 2025: Exploring new narratives for aid in the context of the EU's new strategic agenda - Claire Kumar; Karen Hargrave; Nerea Craviotto; Jessica Pudussery (ODI Europe, 2025)
The aid system is in a moment of significant transition, both due to large budget cuts and the loss of legitimacy of an outdated aid model. Budget cuts are driven by a complex set of factors including austerity, declining living standards in Europe and increasing geopolitical fragmentation and competition. Stakeholders from aid-recipient countries have also delivered a decisive critique of the current aid system. As the development sector seeks to reimagine aid, there is an opportunity to rethink the narratives that drive development cooperation in Europe. This report looks at three related aspects: 1. How narratives around official development assistance (ODA) have shifted in Europe. 2. The narratives emerging with the EU's new priorities and their implications for ODA. 3. Which narratives might have most traction with policy-makers in maintaining robust developmental efforts and ODA spending.
Keywords: 320; Aid; Development finance; Europe